Capital Intensity, Earning Management and Tax Aggressiveness: The Moderation Role of Related Party Transactions - Rahayu, Sri; Trisnawati, Estralita; Firmansyah, Amrie (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to determine the effect of capital intensity and earnings management on tax aggressiveness with related party transactions as a moderator. Actions of tax aggressiveness carried out by the existence of company management policies have an impact on the government. The resulting impacts include declining tax revenues in Indonesia due to a reduction in the tax burden that should be paid. The objects in this study are manufacturing companies listed on the Indonesia Stock Exchange, namely in the period 2016 – 2020. This research uses a quantitative approach, purposive sampling method, and with secondary data. From the criteria set out in this study, a total of 275 company financial reports were obtained for analysis. The results of the tests in this study indicate that earnings management has a significant positive effect on tax aggressiveness, related party transactions are able to moderate and also have a significant positive effect on earnings management on tax aggressiveness. While capital intensity has no effect on tax aggressiveness as well as related party transactions are not able to moderate capital intensity on tax aggressiveness.